Population history of India from the first modern people to the present day - Dyson, Tim (New Delhi Oxford University Press, 2019)
This book presents a history of India's population for the period stretching from when hunter-gatherer homo sapiens first arrived in the country (very roughly seventy thousand years ago) until the modern day. It draws together archaeology, history, and politics to reveal a surprising and often dramatic story.
Includes bibliographical references (pages 281-301) and index.
Keywords: Population; India -- Population; India -- Population -- History; India; History